Mudun Lemah: Integrasi Nilai Tanggung Jawab Berbasis Kearifan Lokal Di Sekolah Dasar - Budi Febriyanto; Mamat Supriatna (Elementary Teacher Education Program, Majalengka University, 2023)
Local wisdom has values that can be integrated in the scope of education. However, in reality, local wisdom is only an activity carried out by the local community without being interpreted into educational values. The purpose of this study is to provide a comprehensive description of the value of mudun lemah in the Kemantren Village community, Cirebon Regency, which can be integrated in education. This research uses a qualitative approach with literature review and field study methods.. Primary data sources are community leaders as informants and primary data sources in the form of documentation in the form of photos and articles. Data collection methods used literature studies, documentation, observation and interviews. Data analysis included data collection, data reduction, and data interpretation. The results of this study reveal that the value of responsibility as the main value and the value of gratitude as a supporting value in Mudun lemah have educational values that can be integrated in elementary school students.